(untitled) (Fiep Bulletin - online, 2014)
Introduction: Thirty percent of premature newborns that need special care and who undergo NICU are at risk of developing brain injuries. Purpose: This study investigated the effects of an immediate intervention program compared to the effects of the same program applied at a later stage, in premature newborns with neuromotor dysfunctions due to hypoxicischemic syndrome. The Denver II scale provided the referential points for analysis of the neurodevelopment motor stage gains achieved with the ISME program. Methods: Forty preterm babies presented signs of Central Nervous System lesions at the Dubowitz tests. The subjects were divided into two groups: the immediate intervention (n=20), and the later intervention (n=20). The pre and post program data were studied through qualitative analysis and non-parametric statistics (Mann/Whitney test), considering the acquired motor stages. Variance analysis revealed a significant statistical difference between data from both groups in all trimesters of the program’s application, with p<0.05 for all considered variables. Results: the first group (of immediate intervention) revealed 100% success in terms of regaining motor normality, showing, at 13 months of corrected age, active gait with normal pattern of posture (static and dynamic) and normal postural reflex mechanisms. The second group, of later intervention, did show a decrease of the abnormal motor patterns and the pathological reflexes. However, after 14 months of intervention, 35% was able to roll, to pass actively to sitting and maintain the position; 40% was able to roll, transition to sitting and four-point; and 25% was able to crawl, transition to standing with support, but was unable to maintain independent stance. Conclusion: The results support the utmost importance of the early application of the I.S.M.E. program starting at the NICU, to promote better results on the motor rehabilitation of newborns with neuromotor dysfunctions, rather then later.